THE EFFECTS OF SUMMARIZING USING INFOGRAPHICS ON EFL LEARNERS’ READING COMPREHENSION. - Dyah Supraba Lastari; Rini Silvana (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
The purpose of this paper is to describe EFL learners’ experiences while using infographics  in a reading class. The pedagogical intervention, based on the use of infographic application (Canva) as an alternative tool to help them summarize reading passages, was implemented to enhance their reading comprehension. The data were gathered from teacher’s journal, questionnaires and the results of students’ reading comprehension tests. The findings revealed that the students viewed the use of infographics could motivate and enabled them to summarize the assigned reading topics much easier. In addition, the assignments incorporating the use of infographic application encouraged them to participate actively in English reading activities in a collaborative atmosphere, allow them to develop their creativity and raise positive attitudes toward the role of technological tools in educational settings.Keywords: English reading, infographics, reading comprehension